Detection of bacterial pathogens in synovial and pleural fluid with the FilmArray Blood Culture Identification System. (2016) - Michos, Athanasios; Palili, Alexandra; Koutouzis, Emmanouil I.; Sandu, Adina; Lykopoulou, Lilia; Syriopoulou, Vassiliki P.
Abstract: We report the use of FilmArray Blood Culture Identification (BCID) multiplex PCR system for pathogen detection from a child with septic arthritis that Streptococcus pyogenes was identified directly from synovial fluid and a child with complicated pneumonia with pleural effusion that Streptococcus pneumoniae was identified from pleural fluid.